THE EFFECTIVENESS OF USING WORDWALL MEDIA IN TEACHING ISLAMIC CULTURAL HISTORY AT MTs YAPDI MEDAN - Zulham; Bilal Hafis (International Journal of Cultural and Social Science, 2025)
This study aims to determine the effectiveness of Wordwall media in improving students' learning outcomes in the subject of Islamic Cultural History (SKI) at MTs YAPDI Medan. Using a mixed-methods approach combining quantitative and qualitative analysis, the research involved pretest and posttest assessments as well as student questionnaires. The results show a significant increase in student learning outcomes, with an average N-Gain score of 0.75, categorized as high. In addition, students responded positively to the use of Wordwall, showing increased motivation, engagement, social interaction, and creativity in the learning process. Wordwall proved to be an effective and engaging digital learning tool, helping students better understand historical material through interactive activities. The study concludes that Wordwall is a highly effective medium for teaching SKI and is recommended for broader application in Islamic education.